2012
DOI: 10.1097/sap.0b013e318214e6ba
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of a Preexisting Scar in the Star-Flap Technique for Nipple Reconstruction

Abstract: It is possible to use a mastectomy scar in the star flap design for nipple reconstruction with no significant vascular compromise. This novel design enables positioning of the nipple in an optimal location on the breast mound in relation with the scar, use of existing scar, and inclusion of extra skin and subcutaneous tissue within the central limb. Nipple projection and volume have been satisfactory and consistently maintained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The use of avascular scar tissue as a free graft harvested from a linear fragment of mastectomy scar, in combination with the healthy skin of a local flap, has been already proposed [10]. Nevertheless, the use of an adjacent mastectomy preexisting scar as donor-site for flaps harvesting has been avoided for many years due to the fear of flap ischemia and necrosis [11,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of avascular scar tissue as a free graft harvested from a linear fragment of mastectomy scar, in combination with the healthy skin of a local flap, has been already proposed [10]. Nevertheless, the use of an adjacent mastectomy preexisting scar as donor-site for flaps harvesting has been avoided for many years due to the fear of flap ischemia and necrosis [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Lesavoy and Liu [11] described in 2010 the diamond double-opposing V-Y flap; this reliable technique showed good results allowing the incorporation of prior mastectomy scars into the flap limbs if they are in the appropriate location. Gurunluoglu et al [12] described in 2012 a star flap technique incorporating a previous scar, and no significant vascular compromise was reported, with acceptable nipple projection and volume. Riccio et al [13] reported in 2015 a V-Y advancement flap which incorporates a previous wise pattern mastectomy or mammaplasty scar into the newly reconstructed nipple, thereby decreasing new scar formation on the breast and leading to favorable cosmetic result.…”
Section: Discussionmentioning
confidence: 99%
“…Most reconstructed nipples retract over time due to scarring and scar contraction, particularly when there has been previous radiotherapy, infection, or poor flap design that compromises the circulation and delays healing. Well established flaps include the skate, 9 star, 10 double-opposing tab flap, 11 - 13 double opposing V-Y flap, 14 and the V-Y advancement flap. 15 …”
Section: Discussionmentioning
confidence: 99%
“…Clinically, it has been reported that the use of flaps elevated from the abdomen with a preexisting scar in the midline and subsequent use in breast reconstruction increased the necrosis rates [ 10 12 ]. In addition, no vascular problem was observed in nipple reconstruction techniques in which the mastectomy scar was included [ 13 ]. Although these studies provide very valuable information, the reliability of standard flaps planned from tissues that have experienced recent trauma or in which there was a scar in the midline was not evaluated.…”
Section: Introductionmentioning
confidence: 99%